PENGARUH FAKTOR-FAKTOR BAURAN PEMASARAN JASA TERHADAP KEPUTUSAN KONSUMEN UNTUK MENGINAP DI HOTEL BINTANG LIMA KOTA PALEMBANG - Muhammad Iqbal (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
The approach taken in this study is a quantitative approach in the form of associative because this study aims to explain the relationship between two or more variables, namely product, price, place, promotion, people, physical facilities, and processes (independent variables) to the decision to stay overnight (dependent variable ). The purpose of this study was to determine and analyze the effect of jointly and partially the marketing mix (product, price, promotion, place, people, and physical evidence) on the consumer's decision to stay at the Five Star Hotel in Palembang. The results of this study conclude, first, all marketing mix variables (products, prices, promotions, location, people, processes and physical evidence) have an influence on the decision to stay at a Five Star Hotel. Second, partially the product variable, price, promotion, people and physical evidence of the variable variable have a significant effect, while the Location and Process Variables have no significant effect on the decision to stay at a Five Star Hotel. Third, the Price Variable, has a dominant influence on the desires / decisions of consumers / customers / guests to stay at five-star hotels, especially at the Whyndam OPI Hotel and The Excelton Hotel Palembang. Based on the conclusion, the researcher gave a suggestion. first, the hotel manager recalculates the tariff / price set so that it can provide greater discounts, and improve hotel facilities including the design and comfort of hotel rooms. Second, adding hotel facilities including improving the quality of design and comfort of hotel rooms. Third, for further research, other variables can be added outside the marketing mix to complement the results of subsequent studies regarding the decision to stay at a five-star hotel.